A critical study of the viability of the personal data protection legal framework in Malaysia: with special reference to the EU and the UK legal frameworks / Mohd Bahrin Othman - Othman, Mohd Bahrin (2009)
Globalisation and the advancement of the ICT have created new risks in the processing of personal data. Personal data is now perceived as a commodity at the expense of the individual information privacy. The personal data protection strives to provide the remedy of past injustices caused by inadequate protection of personal information. The issue of personal data protection is part of the broader debate on the best way to protect personal information. It is also part of a much wider debate about the governance of the personal data protection. The aim of this study is to propose a viable legislative model for personal data protection legal framework in Malaysia. It underscores the conflicting interests between the individual information privacy and trade interest. The legal chapters (Chapters 3 and 4) provide an account of the data protection legal frameworks in the European Union, the UK and Malaysia, focusing on the protection of individual information privacy within the ambit of the said frameworks and the critiques that can be levelled against them. The findings chapter (Chapter 5) reports on the fieldwork findings often respondents, conducted to investigate their perceptions on the protection of personal data in Malaysia. The central arguments of this thesis are that firstly, there is a dire need to have a personal data protection law in Malaysia. Secondly, it is imperative for the policy makers to incorporate a prescriptive top-down comprehensive command and control Personal Data Protection Act. The research will provide the knowledge on the viable legislative model of personal data protection legal framework for Malaysia which confers a degree of protection for personal information that has not previously existed in Malaysia. It will contribute to the literature on personal data protection law, which would attempt to redress the tensions and conflict between individuals and trade interests.